DEVELOPMENT OF LANGUAGE PSYCHOLOGY IN ELEMENTARY SCHOOL CHILDREN AND ITS LEARNING IMPLICATIONS AT SDN SUMBER 2 YOGYAKARTA - lanovianti, yeni novita; Khosiyono, Banun Havifah Cahyo (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
A child’s language development involves a combination of social interaction, emotions, physical and motor skills, and cognition. During the progress of learning in elementary school, educators should be able to align the curriculum with students’ developmental levels. Many factors are crucial in language development, including biological factors and experiences. Culture also plays a significant role in daily communication for children and adults. This research aims to understand the Psychological Language Development in Elementary School Children and its implications for learning. This research utilizes a qualitative descriptive method based on articles related to the language development characteristics of elementary school students. The data collection for this research is through interviews. The results of this research indicate that language development in elementary school children primarily involves pragmatic, semantic, and syntactic development.